Histological study of potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazole-3-yl)thio)acetate (PKR-173) corrective influence on the chickens liver state in the condition of tetracycline hepatitis - R. O. Shcherbyna; Ye. V. Vashchyk (Zaporožskij Medicinskij Žurnal)
Despite great scientific progress in the sphere of hepatoprotectors development during recent years, the issues of hepatocytes protection and regeneration is relevant enough. In this aspect derivatives of heterocyclic systems are of great interest, in particular, of 1,2,4-triazole.